Utilization and Accessibility for Pedestrian Bridges at Ahmad Yani and Sugiyapranata Street, Semarang - Abdillah, Adib; Wibawa, Baju Arie (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2020)
Abstract. The pedestrian bridge is a facility built to provide comfort and safety for a pedestrian. The pedestrian bridge can also be interpreted as a pedestrian facility to cross busy and full roads, cross highway road, or railroad line so that the flow of circulation people and vehicles can be separated and minimize accidents. The purpose of this study is to analyze whether the pedestrian bridge in Semarang has met the standards, at the Ahmad Yani street, the pedestrian bridge there are still many who do not use these facilities. The method used is qualitative research with direct observation methods. As a result, the two pedestrian bridges do not safety and comfort standards, so the level utilization is lower (about 27-37%).Â Keywords: pedestrian, pedestrian bridge, accessibility, disabled people, street